Party Hacks and True Believers: The Effect of Party Affiliation on Political Preferences - Eric D. Gould; Esteban F. Klor (Journal of Comparative Economics, 2019)
This paper examines the effect of party affiliation on an individual’s political views.  To do this, we exploit the party realignment that occurred in the U.S. due to abortion becoming a more prominent and highly partisan issue over time.  We show that abortion was not a highly partisan issue in 1982, but a person’s abortion views in 1982 led many to switch parties over time as the two main parties diverged in their stances on this issue.  We find that voting for a given political party in 1996, due to the individual’s initial views on abortion in 1982, has a substantial effect on a person’s political, social, and economic attitudes in 1997.  These findings are stronger for highly partisan political issues, and are robust to controlling for a host of personal views and characteristics in 1982 and 1997.  As individuals realigned their party affiliation in accordance with their initial abortion views, their other political views followed suit.